1970
DOI: 10.1037/h0029477
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to extinction in the rat following regular and irregular schedules of partial reward.

Abstract: Four groups of rats were trained in a runway for 28 days on one of the following schedules: consistent reward (CRF), alternating partial reward (A), alternating partial reward followed by consistent reward (A-CRF), and an irregular partial reward schedule (I). Both Groups A and A-CRF learned to run faster on rewarded trials than on ronrewarded trials and Group A-CRF quickly learned to run rapidly on all trials after being shifted to consistent reward. Resistance to extinction was greatest for Groups A-CRF and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

1971
1971
1988
1988

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 8 publications
1
21
0
Order By: Relevance
“…The results obtained under immediate extinction were consistent with those of previous studies (e.g., Campbell, Knouse, & Wroten, 1970;Capaldi, 1958;Capaldi & Minkoff, 1967;Habu & Ono, 1969;Tyler, Wortz, & Bitterman, 1953) and were predictable from the sequential variables (Capaldi, 1967). However, the rest of the results, including the PRDE, cannot be explained by these variables.…”
supporting
confidence: 83%
“…The results obtained under immediate extinction were consistent with those of previous studies (e.g., Campbell, Knouse, & Wroten, 1970;Capaldi, 1958;Capaldi & Minkoff, 1967;Habu & Ono, 1969;Tyler, Wortz, & Bitterman, 1953) and were predictable from the sequential variables (Capaldi, 1967). However, the rest of the results, including the PRDE, cannot be explained by these variables.…”
supporting
confidence: 83%
“…Campbell et al (1970) have shown that patterning reduces resistance to extinction. In the present study.…”
Section: Bloom Williams and Metzementioning
confidence: 99%
“…This theory, of course, accounts nicely for the observed interaction. Irregular schedules have longer N lengths than alternating schedules, but the irregular schedule has fewer N-R transitions.Campbell, Knouse, and Wroten (1970) suggested that an additional variable was operating to produce the difference in extinction performance between alternating and irregular schedules after extended training. Rats given extended training on alternating schedules typically learn to run rapidly on trials followRequests for reprints should be sent to…”
mentioning
confidence: 99%
“…Campbell, Knouse, and Wroten (1970) suggested that an additional variable was operating to produce the difference in extinction performance between alternating and irregular schedules after extended training. Rats given extended training on alternating schedules typically learn to run rapidly on trials followRequests for reprints should be sent to…”
mentioning
confidence: 99%
See 1 more Smart Citation